Making Sense of an Ancient Discipline in a Modern Time: How Tai Chi (太极) Practice Benefits the Body-Mind - Meghdad Abdi (Wolters Kluwer Health/LWW, 2019)
Tai chi(太极) is an ancient Chinese traditional martial art that, today, is also practiced as a graceful and multifaceted form of exercise. It involves a series of movements performed in a slow, focused manner accompanied by deep breathing and expanded awareness of the body, mind, and surrounding environment. There is growing evidence that this mind-body practice has value in treating or preventing many health problems and you can get started even if you are not in top shape or the best of health. This paper is a review of the research that has been conducted internationally on the health-enhancing aspects of Tai Chi practice over the past few years. It is not possible to cover all areas of research in one paper; therefore, three important areas are chosen and discussed, namely, improving balance, strengthening the bones, reducing pain and the rest will be referred to in a future article.